Duplex dual‐labeled fluorescence probe‐based melting curve and endpoint genotyping assays for genotyping of rs2000999 and haptoglobin gene deletion - Soejima, Mikiko; Koda, Yoshiro (Electrophoresis, 2022)
Haptoglobin (Hp) is a hemoglobin‐binding serum glycoprotein. Some variations in the Hp gene (HP) or Hp‐related gene (HPR), including a single‐nucleotide polymorphism in intron 2 of HRP, rs2000999, and a complete deletion of the HP gene (HPdel), one of the rare variants of HP, have been reported to correlate with the serum cholesterol concentration as well as the serum Hp concentration. In this study, we developed a duplex dual‐labeled fluorescence probe‐based method to simultaneously determine the rs2000999 G > A polymorphism by melting curve genotyping and the zygosity of HPdel by endpoint genotyping. This method was then validated by using the genomic DNA from 94 Japanese subjects for whom genotypes of rs2000999 and HPdel zygosity had already been determined. The results obtained with this method were in perfect agreement with the previous ones. Thus, the present method enables us to estimate these two polymorphisms in relatively large‐scale groups of subjects, especially in Asian populations where the HPdel is distributed.